2016
DOI: 10.1364/ao.55.007412
|View full text |Cite
|
Sign up to set email alerts
|

Proximity operators for phase retrieval

Abstract: We present a new formulation of a family of proximity operators that generalize the projector step for phase retrieval. These proximity operators for noisy intensity measurements can replace the classical "noise free" projection in any projection-based algorithm. They are derived from a maximum likelihood formulation and admit closed form solutions for both the Gaussian and the Poisson cases. In addition, we extend these proximity operators to undersampled intensity measurements. To assess their performance, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Most of the phase retrieval algorithms are based on the Gerchberg-Saxton algorithm [8]: ER [2], HIO [2], shrinkwrap [9], charge-flipping algorithm [25], relaxed averaged alternating reflections (RAAR) algorithm [26], noise tolerant HIO algorithm [18], and many others [10]. The main differences between these algorithms are the various constraints applied in real space [2,9,20,24] and reciprocal space [27][28][29], which can be optimized depending on the particular sample and experiment. Moreover, a combination of phase retrieval algorithms (ER and HIO algorithms [2,24,30]) is often applied in an alternating fashion to avoid stagnation or oscillation of the iterative process and to stabilize the final reconstruction.…”
Section: Optimized Phase Retrieval Algorithmsmentioning
confidence: 99%
“…Most of the phase retrieval algorithms are based on the Gerchberg-Saxton algorithm [8]: ER [2], HIO [2], shrinkwrap [9], charge-flipping algorithm [25], relaxed averaged alternating reflections (RAAR) algorithm [26], noise tolerant HIO algorithm [18], and many others [10]. The main differences between these algorithms are the various constraints applied in real space [2,9,20,24] and reciprocal space [27][28][29], which can be optimized depending on the particular sample and experiment. Moreover, a combination of phase retrieval algorithms (ER and HIO algorithms [2,24,30]) is often applied in an alternating fashion to avoid stagnation or oscillation of the iterative process and to stabilize the final reconstruction.…”
Section: Optimized Phase Retrieval Algorithmsmentioning
confidence: 99%
“…This was rigorously demonstrated by Bauschke et al [41] since Fienup's BIO and HIO are shown to be instances of Dykstra and Douglas-Rachford algorithms. In [12], alternating projections strategies are reformulated as proximity operators derived from the maximum likelihood point of view.…”
Section: The Alternating Projections Point Of Viewmentioning
confidence: 99%
“…Most phase retrieval techniques are still derived from the methods of alternating projections initially proposed by Gerchberg and Saxton [3] and popularized and extended by Fienup [4,5]. This class of methods is still widely used today [6][7][8][9][10][11][12][13], with improvements to enforce a priori knowledge (support of the objects, admissible values domain, sparsity constraints) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we benefit from the closed-form expressions that have been recently derived for Gaussian likelihood in [49]. In the present work, we consider the weighted quadratic data-fidelity term…”
Section: Proximity Operator For Phase-retrievalmentioning
confidence: 99%